Wild ducks at the New Grounds 1947-57 - Anonymous, Anonymous (Wildfowl, 1957)
The first five Trust Reports included notes on the status of ducks on the Severn estuary. These short annual summaries were discontinued because they seemed largely repetitive and of merely parochial interest. This review of ten years of observation has two claims on the attention. First, as a summary of apparent changes in the status of species visiting the estuary of the Severn and second, as a report on the effects of the development of the Trust collection on the numbers and habits of the ducks frequenting Berkeley New Decoy and the pens and enclosures which have gradually been constructed around it. The two are in practice not separate, for there is constant traffic between the river and the pens; but for some species it is appropriate as well as convenient to write as if they were.